Use of humor in the virtual classroom: characterization of teacher perspectives - Toribio López, Alexander; Palacios Nuñez, Madeleine Lourdes; Deroncele Acosta, Angel (LACCEI, 2024)
The use of humor in the classroom by teachers plays a strategic and pedagogical role in facilitating teaching and student learning. The objective of the study was to characterize university teachers' perspectives on the use of humor in the virtual classroom. To achieve this, a quantitative approach, descriptive in scope, was used, using the survey technique. A questionnaire was applied to 259 teachers from a private university in Lima. It is found that 96% of the teachers use humorous elements in their virtual classes and show a marked preference for the use of humorous narration, above the use of humorous visual resources. In addition, teachers consider that humor improves attention, motivation and closeness with the student. Finally, 86% of university teachers completely agree or agree that humor is a competence they can develop, so universities should implement training strategies to develop the Humorous Teaching Competence in university teachers.